Penerapan Model Project Based Learning Dalam Meningkatkan Hasil Belajar PAI Di Kelas X SMK Negeri 1 Padang - Dirizki, Yandra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) by implementing the Project-Based Learning (PBL) model on the topic "Competing in Goodness and Work Ethos." The research was conducted in two cycles, with evaluations carried out through learning tests and observations of student activities. The results of the study show that the application of the PBL model successfully improved student learning completion, reflected by a completion percentage of 85% in cycle II. Additionally, the PBL model enhanced students’ confidence in presentations and discussions, as well as their ability to collaborate in groups. This study concludes that PBL can be an effective method for improving student learning outcomes in the context of PAI.